Knowledge, Attitudes, and Healthy Feeding Behavior of Mothers on the Nutritional Status of Elementary School Students - Liemen, Sherin Felicia; Kurniawan, Felicia; Djaya, Nanny (Faculty of Medicine Universitas Padjadjaran, 2023)
Background: Some children aged 6-9 years have started to enter the pre-pubertal rapid growth period. Therefore, the need for nutritious food has begun to increase significantly. The role of mothers in providing food is very much needed. This study aimed to discover the relationship between knowledge, attitudes, and behavior of mothers in healthy feeding on the nutritional status of children.Methods: This study was a cross-sectional study conducted in July–August 2019. The sample was mothers and their children who were in grades I to III of public and private elementary schools in Penjaringan, Jakarta. The total sampling method was conducted, and data collected included age, gender, height, weight, and mother’s knowledge, attitudes and behavior in healthy feeding Data was analyzed using Chi-square. The nutritional status of the students was calculated using the 2010 anthropometric standards of the Ministry of Health.Results: Of the 348 mothers included, there were 310 mothers (89.1%) with high level of knowledge, 86.5% of mothers had a positive attitude, and 75.3% had good behavior in healthy feeding. The nutritional status of the children was predominantly normal (46.2%) and overweight (34.8%). There was a significant relationship between maternal behavior in giving healthy food and children nutritional status (p=0.046).Conclusions: There is a significant relationship between the mother's behavior in offering healthy food and the children nutritional status. Therefore, parents should pay more attention to behavior in providing healthy food to children.